Annals of Scientific Society for Assembly, Handling and Industrial Robotics - Schüppstuhl, Thorsten; Tracht, Kirsten; Henrich, Dominik (Springer Berlin Heidelberg : Imprint: Springer Vieweg, 2020)
This Open Access proceedings presents a good overview of the current research landscape of industrial robots. The objective of MHI Colloquium is the successful networking at both academic and management level. Thereby, the colloquium focuses an academic exchange at a high level in order to distribute the obtained research results, to determine synergy effects and trends, to connect the actors in person and in conclusion, to strengthen the research field as well as the MHI community. In addition, there is the possibility to become acquatined with the organizing institute. Primary audience is formed by members of the scientific society for assembly, handling and industrial robotics (WGMHI). The Editors Prof. Dr.-Ing. Thorsten Schüppstuhl is head of the Institute of Aircraft Production Technology (IFPT) at the Hamburg University of Technology. Prof. Dr.-Ing. Kirsten Tracht is head of the Bremen Institute for Mechanical Engineering (bime) at the University of Bremen. Prof. Dr. Dominik Henrich is head of the RESY Research Lab at the University of Bayreuth. .